TANTANGAN PEMANTAU PEMILU DALAM MENJAGA HAK PILIH TAHUN 2024 - Telaumbanua, Revorlin; Telaumbanua, Yoses Ondrasi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Historically recorded elections (elections) in 2019 were general elections held in Indonesia. This is a form of implementation by the Constitutional Court (MK) Decision Number 14/PUU/2013 regarding the review of Law Number 42 regarding the election of the President and Vice President. Political parties that have been carried out in general are considered to have experienced severe problems for election organizers which resulted in thousands of casualties in the implementation of the 2019 elections, and also resulted in technical errors of the implementers. With various existing problems, it is a challenge to face the 2024 political year. This paper will focus on the Challenges of Election Monitoring (General Elections) in Maintaining Voting Rights in 2024. This paper will focus on the Challenges of Election Monitoring (General Elections) in Maintaining Voting Rights in 2024. The research method used is The data obtained by the author is carried out through library research (literature research) and based on data obtained through journals and websites in accordance with the title of the article.Keywords : Monitoring, General Election